Using the Emergenetics Training and Profile as a Study and Development Tool in the College Classroom (Journal on Excellence in College Teaching, 2024)
One of the most important processes in which professors can engage is to explore different techniques to improve the learning environment. Zull (2002, 2011) has stated that people adopt new learning by "idea testing." Was the test beneficial? The authors, who were interested in testing ideas to improve the teaching and learning process, collaborated to investigate the Emergenetics Profile (EP) as a college teaching and learning support tool. The study reveals student and instructor perceptions and beliefs about the EP to draw conclusions, recognize limitations, and plan for additional investigation of this process.